Critical success factors, opportunities and threats of the cost management profession: the case of Australasian quantity surveying firms. (1st January 2013) - Frei, Marcel; Mbachu, Jasper; Phipps, Robyn
The quantity surveying profession faces a number of exceptional challenges that threaten its existence, growth and success. The aim of this paper is to identify the critical success factors (CSFs) for growth and survival as well as the threats and opportunities in the external landscape. Knowledge of these factors would enable the profession to achieve sustained growth and competitiveness. Using the exploratory survey method, in-depth interviews were conducted with key senior leaders from industry and professional and academic institutes throughout New Zealand and Australia. Results showed that the CSFs of the profession are underpinned by process, practice management, service performance, market positioning, people, firm profile and professional attributes. Four themes underlie the threats and opportunities of the profession, namely: market/competition, capability/capacity, recognition/relevance, and information/communication/technology. Identified opportunities stem mainly from involvement in newly identified or emerging markets, and expansion in or penetration of existing markets.